Sabbath Keeping and Its Relationships to Health and Well-Being: A Mediational Analysis - Superville, Devon J. (The international journal for the psychology of religion, 2014)
Prior research showing positive relationships between indicators of religiousness and health has generally defined and measured religion broadly. In addition, researchers have not given much attention to the pathways through which the relationship between religion and health is maintained. The result is a lack of specificity that fails to address questions about how and why religion is associated with health. The present study sought to address these limitations and clarify the ties between religion and health through a finer grained analysis of one specific aspect of religiousness (Sabbath keeping) and four possible mediators (religious coping, religious support, diet, and exercise) through which it might affect health. We examined data from a sample of Seventh-day Adventists in North America (N = 5,411), and bootstrapping analysis revealed that the association between Sabbath keeping and physical and mental health was partially mediated by all four mediators. Implications and limitations of the findings are discussed.